2021
DOI: 10.1002/jcla.23752
|View full text |Cite
|
Sign up to set email alerts
|

Development of quantum dot‐based fluorescence lateral flow immunoassay strip for rapid and quantitative detection of serum interleukin‐6

Abstract: Background Interleukin‐6 (IL‐6) is an inflammatory factor that increases rapidly in response to infectious diseases including sepsis. The aim of this study is to develop a quantum dot (QD)‐based fluorescence lateral flow immunoassay (LFIA) strip that can rapidly and accurately detect IL‐6 levels. Methods QD‐based LFIA strips were fabricated by conjugating CdSe/ZnS QDs to the IL‐6 antibody. Performance verification and clinical sample analysis were carried out to evaluate the newly developed strip. Results QD‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…2d) enabled the detection down to 93 fg ml −1 (Fig. 2e, five-parameter logistic fit), which represents a 1,785-fold improvement in the LOD compared with conventional AuNP-based LFAs and at least an order of magnitude higher than the previously reported LFAs [43][44][45][46] . The LOQ of fluorometric p-LFA (298 fg ml −1 ) is 2,288-fold better than the LOQ of colorimetric LFA (682 pg ml −1 ).…”
Section: P-lfa For Quantitative Detection Of Human Il-6mentioning
confidence: 70%
“…2d) enabled the detection down to 93 fg ml −1 (Fig. 2e, five-parameter logistic fit), which represents a 1,785-fold improvement in the LOD compared with conventional AuNP-based LFAs and at least an order of magnitude higher than the previously reported LFAs [43][44][45][46] . The LOQ of fluorometric p-LFA (298 fg ml −1 ) is 2,288-fold better than the LOQ of colorimetric LFA (682 pg ml −1 ).…”
Section: P-lfa For Quantitative Detection Of Human Il-6mentioning
confidence: 70%
“…The coefficients of variation (CVs) at each concentration were below 15%. 39 Compared to mCNAN-mLFIA, the CV of intra-assay precision was decreased by 3.45% for the Tc line and 5.39% for the Ts line (Figure 4A,B), while the CV of the interassay precision was decreased by 8.29% for the Tc line and 13.19% for the Ts line for CNAN-mLFIA (Figure 4C,D). The CV of CNAN-mLFIA was <15% in all cases, indicating that higher precision can be obtained for CNAN-mLFIA.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The interassay precision was determined on 10 consecutive days with two replicates. The coefficients of variation (CVs) at each concentration were below 15% . Compared to mCNAN-mLFIA, the CV of intra-assay precision was decreased by 3.45% for the Tc line and 5.39% for the Ts line (Figure A,B), while the CV of the interassay precision was decreased by 8.29% for the Tc line and 13.19% for the Ts line for CNAN-mLFIA (Figure C,D).…”
Section: Resultsmentioning
confidence: 96%
“…In another work, Luo et al also fabricated an IL-6 antibody immobilized CdSe/ZnS QDs-based fluorescence lateral flow immunoassay (LFIA) strip for selective detection of IL-6 in human serum. 187 Recently, Wu et al successfully demonstrated a new approach using fluorescent titanium nanoclusters (Ti NCs) for highly selective sensitive detection of CK-MM in myocardial infarction. 188 The sensing phenomenon of Ti NCs is the strong binding nature with the phosphate group of ATPS, in which the creatine was converted into phosphocreatine as shown in Figure 7c.…”
Section: Optical Signaling Readout-based Nanobiosensorsmentioning
confidence: 99%